Spatial Ability among the Students with Learning Disabilities in Hail and its Relation with Some Variables - Khasawneh, Mohamed (Jordan Journal of Educational Sciences, 2013)
This study aimed at investigating the development of spatial ability among the learning disabilities students in Hail and its relationship with some variables in addition to identifying the individual differences in performance on the spatial ability test and relationship with the variables of grade, the type of learning disability, and gender belonging to the directorate of education in Hail. The sample consisted of (221) students chosen randomly from different schools, then they responded to a mental rotation test to measure the spatial ability. The results showed that there were no significant differences in the performance on the test of spatial ability due to the grade level; the gender, nor the type of learning disabilities. In light of the results, there were some recommendations.